Long-term mechanical circulatory support: evolution, present milestones, and future directions - R. Yu. Bangarov; T. A. Khalilulin; V. M. Zakharevich; Sh. R. Galeev; G. V. Nabiev (Вестник трансплантологии и искусственных органов, 2025)
Objective: to examine the historical evolution, current advancements, and future prospects of long-term mecha nical circulatory support (LT-MCS) devices in the management of end-stage heart failure.Materials and methods. An analysis was conducted on clinical studies (MOMENTUM 3, INTERMACS, EUROMACS), historical records, and technological progress in the field of LT-MCS. The review covered three generations of devices: pulsatile pumps (first generation), axial-flow pumps (second generation), and centrifugal pumps with magnetic levitation (third generation). Key outcomes evaluated included survival rates, complication rates (thrombosis, infections, right ventricular failure), and developments within national technology.Results. The HeartMate III third-generation device has a 2-year survival rate of 82% with a pump thrombosis risk of less than 1%. However, complications remain, including driveline infections (10–15%), right ventricular failure (20–40%), and bleeding events (15–20%). Domestic systems (Stream Cardio) are comparable to second-generation devices but lag in terms of miniaturization and clinical trials. Emerging technologies like the Leviticus FiVAD wireless energy transfer system and the Carmat Aeson fully implantable artificial heart are opening up promising new directions for the future of mechanical circulatory support.Conclusion. Modern LT-MCS systems have emerged as a via- ble alternative to heart transplantation (HT), particularly for patients who are not candidates for HT. Key areas of ongoing development include device miniaturization, wireless energy transfer technologies, and integration of artificial intelligence. The future of LT-MCS will largely depend on overcoming current system limitations, notably the risks of infection and right ventricular failure.